MARKETING MODEL OF ROYAL DUTCH AIRLINES: TECHNICAL AND CONCEPTUAL SUSTAINABILITY - Susilo, Daniel; Mendoza, Carlo Magno T. (RADJA PUBLIKA, 2023)
Digital age makes everything is open source and easy to access through internet or application and that includes big company such as Royal Dutch Airlines. The influence of the internet helps to grow sustainability marketing developed by KLM airline. With the SWOT analysis, Author is able to discover that their key of both preserving environment and sustainability development itself is through technical and conceptual marketing development of low emission flight and biofuel flight. This analysis helps the audience to find that sustainability marketing development is a long practical journey instead of quick spread in numbers of campaigns and promotions.